OPTIMIZATION OF UNIT KAMSEL THROUGH PENERANGAN KELILING TO REDUCE THE ACCIDENT RATE IN THE KARANGANYAR POLICE JURISDICTION AREA - RAJA RIZKI SIHOMBING (Advances in Police Science Research Journal, 2022)
High traffic accidents are one of the lists of disturbances in the security and social order in the jurisdiction of the Karanganyar Police. Basically the Karanganyar Resort Police through the Satlantas Kamsel Unit has a major role in controlling and preventing accidents by carrying out preventive efforts through street lighting. The implementation of street lighting routinely runs well but is not optimal, this can be seen from the number of traffic accidents in the Karanganyar Police jurisdiction which is still fluctuating in the last 4 years. This situation motivated researchers to conduct more in-depth research on the topic of Optimizing the South Kamsel Unit through Mobile Information to Reduce Accident Rates in the Karanganyar Police Legal Area. The research was conducted using a qualitative research approach with a descriptive type of research that aims to provide a description, explanation, and validation of the phenomenon under study. This research is also supported by data collection techniques in the form of observations, interviews and documentation studies through documents. Then the data that has been obtained is then validated for truth through triangulation and determining the data to be used through data reduction, data presentation and determining conclusions. The findings of the study were then analyzed further and then analyzed using management theory and SWOT theory. In the end, the researcher was able to find the problem and was able to answer it through the symptoms that occurred in the form of a circular lighting process which was assessed based on the Implementation Instructions of the National Police Chief No. Pol: 5/V/ 2003 concerning Public Education in the Traffic Sector. Circular lighting is one of the effective preventive efforts when viewed from the process, but maximum results cannot be shown optimally in a sustainable manner. This is influenced by internal and external factors of the Police